Laser‐induced stainless steel mesh for high effective water/oil separation. (1st January 2018) - Chen, Tianchi; Liu, Hongtao; Yang, Haifeng; Yan, Wei; Zhu, Wei; Liu, Hao; Guo, Kaijin
Abstract : The hierarchical micro/nano structures are successfully obtained on the stainless steel mesh via a simple laser direct writing technology. The as‐prepared mesh reveals excellent superhydrophilic/underwater superoleophobic properties or superhydrophobic/superoleophilic properties after 1H, 1H, 2H, 2H‐perfluorodecyltriisopropoxysilane modification. According to the oil density, the superhydrophilic/underwater superoleophobic mesh allows water to permeate and repels the light oil. Its oil/water separation efficiency is as high as 98.5% for the light oil. The superhydrophobic/superoleophilic mesh can be easily wetted by heavy oils while the water will be repelled, which the separation efficiency can reach 98.0% for the heavy oil. Moreover, this special wettability mesh can still maintain high separation efficiency after 20 separation cycles, which indicates the good separation stability.